Phosphorus attenuation and mobilization in sand filters treating onsite wastewater - Mian Wang; Fanjian Zeng; Siwei Chen; Laura M. Wehrmann; Stuart Waugh; Bruce J. Brownawell; Christopher J. Gobler; Xinwei Mao (Chemosphere, 2024)

Biogeochemical plumbing of pioneer mangrove intertidal flats in French Guiana - Robert Aller; Issac Klingensmith; Thomas Stieglitz; Christina Heilbrun; Stuart Waugh; Adelaide Aschenbroich; Gerard Thouzeau; Emma Michaud (Regional Environmental Change, 2024)
Migrating mudbanks are characteristic features of the vast Amazon-Guianas coastline along Northeastern South America. As illustrated by sites in French Guiana, consolidating mudflats that periodically transition to mangrove forest are permeated by extensive crustacean burrow systems, sometimes in isolation but more often in close association with morpho-sedimentary structures such as tidal pools and channels. Burrow structures are critical to mangrove growth. In this study, we evaluated the ways in which burrows act as complex conduits that plumb deposits for solute exchange with overlying water. We sampled burrows during low tide when irrigation is inhibited and burrow water rapidly becomes anoxic. The products of diagenetic reactions, for example: NH 4 + , N 2 , and Si(OH) 4 , build up with time, revealing sedimentary reaction rates and fluxes. When oxygenated, burrow walls are zones of intense coupled redox reactions such as nitrification-denitrification. Build-up often is lower in burrows connected directly to tidal pools where photosynthetic activity consumes remineralized nutrients, and burrows can remain periodically irrigated at low tide. During flood, burrows, particularly those that connect tidal pools laterally to channels, can be rapidly flushed and oxygenated as channel water rises and then spreads across flats. Burrow flushing produces enhanced concentrations of nutrients within the leading edge of the flood as seawater moves progressively towards and into adjacent mangroves. Estimates of burrow volumes obtained from drone surveys together with burrow solute production rates allow upscaling of burrow-sourced metabolite fluxes; however, these are extremely variable due to variable burrow geometries, connections between burrows, pools, and channels, and burrow water residence times (oxygenation). The flushing of burrows during flood results in a rectification of sediment-water fluxes shoreward and enhances the delivery of nutrients from the flats into adjacent mangroves and pools, presumably stimulating colonization and forest growth.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Association mapping of malting quality traits in UK spring and winter barley cultivar collections - Mark E. Looseley; Luke Ramsay; Hazel Bull; J. Stuart Swanston; Paul D. Shaw; Malcolm Macaulay; Allan Booth; Joanne R. Russell; Robbie Waugh; William T. B. Thomas (Theoretical and Applied Genetics, 2020)
Key message Historical malting quality data was collated from UK national and recommended list trial data and used in a GWAS. 25 QTL were identified, with the majority from spring barley cultivar sets. Abstract In Europe, the most economically significant use of barley is the production of malt for use in the brewing and distilling industries. As such, selection for traits related to malting quality is of great commercial interest. In order to study the genetic basis of variation for malting quality traits in UK cultivars, a historical set of trial data was collated from national and recommended list trials from the period 1988 to 2016. This data was used to estimate variety means for 20 quality related traits in 451 spring barley cultivars, and 407 winter cultivars. Genotypes for these cultivars were generated using iSelect 9k and 50k genotyping platforms, and a genome wide association scan performed to identify malting quality quantitative trait loci (QTL). 24 QTL were identified in spring barley cultivars, and 2 from the winter set. A number of these correspond to known malting quality related genes but the remainder represents novel genetic variation that is accessible to breeders for the genetic improvement of new cultivars.

Crops that feed the world 4. Barley: a resilient crop? Strengths and weaknesses in the context of food security - Adrian Clive Newton; Andrew J. Flavell; Timothy S. George; Philip Leat; Barry Mullholland; Luke Ramsay; Cesar Revoredo-Giha; Joanne Russell; Brian J. Steffenson; J. Stuart Swanston; William T. B. Thomas; Robbie Waugh; et al. (Food Security, 2011)

Albatross predation of juvenile southern blue whiting ( Micromesistius australis ) on the Campbell Plateau - Yves Cherel; Sue Waugh; Stuart Hanchet (New Zealand Journal of Marine and Freshwater Research, 1999)
Dietary samples collected at Campbell Island in summer 1997 indicate that southern blue whiting ( Micromesistius australis ) formed the bulk of the food of black‐browed albatrosses ( Diomedea melanophrys impavida ) during the chick‐rearing period. Birds preyed upon a single size class of fish with a mode at 80–90 mm standard length; fish were 4–5 months old and belonged to the + age group. Satellite tracking showed that, when performing trips of short duration, adult albatrosses foraged within the 1000 m depth contour in the subantarctic zone north of Campbell Island. The feeding ecology of albatrosses thus suggests that juvenile (+) southern blue whiting are pelagic and occur in dense schools in the top 5 m of the water column over the Campbell Plateau during the summer months. The high reliance of birds on juvenile southern blue whiting during the chick‐rearing period has implications for the management of the southern blue whiting fishery and the conservation of black‐browed albatrosses and other marine predators occurring in the New Zealand subantarctic area.